Hamlet e Sons of Anarchy: modelização das personagens do teatro à ficção seriada televisiva - Lima, Virgínia Duan Araújo de Alcântara e (2019)
This research aims to realizes an investigation of the structuring and interaction of the different semiotics languages, as well as the semiosis produced from these dialogically interacts. In this perspective, our study seeks to understand how happen the resignification of the dramatic text Hamlet (1599-1601), by William Shakespeare; throught the construction of the television series Sons of Anarchy (2008-2014), by Kurt Sutter. The category of the character will be considered as a sign modeling in the process of dialogue between works of art of different languages, observing its modeling process from the Russian studies on the Semiotics of Culture. In this way, this research intends to contribute to the understanding of the mentioned works as semiotic texts that are resignified in constant creative movement.